A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMP 40 PEKANBARU IN COMPREHENDING DESCRIPTIVE TEXTS - Harkoni, Rio Saputra; Aruan, Rumiri Rotua; Erni, Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This descriptive research is aimed at finding out the ability of the second year students of SMP 40 Pekanbaru in comprehending descriptive texts. The research data were collected from March 15th to October 25th 2018. The subject of this research is class II.3 which consists of 30 students. The data were collected by administering a test to the students in the form of multiple choice type. The test consists of 30 items. Based on the research, it was found out that first: the ability of the second year students in reading comprehension is classified into good level with the mean score of 77.4. Second, the students’ mean score in finding main ideas was classified into good level with the mean score of 78.4, finding the factual information was classified into excellent level with the mean score of 87.5, in finding the meaning of vocabulary was classified into good level with the mean score of 79 , in finding references was classified into good level with the mean score of 74, in finding inferences was classified into good level with the mean score of 68. As a conclusion, the ability of the second year students of SMP 40 Pekanbaru in comprehending descriptive texts fall into average to good level with mean score 77.4. It is recommmended that the students must do more practice and read books to improve reading skills. Next, the teacher should have more effort to develop the students’ motivation and encourage them to practice in comprehending the text.Key Words: Reading Ability, Comprehending Descriptive Texts.